Manajemen Pendidikan Islam Menurut Al-Quran: Analisis dan Implementasi - Alfaniah, Afifi; Fauji, Imam (Lembaga Yasin AlSys, 2025)
Islamic education aims to develop human potential both physically and spiritually, so that individuals can carry out their role as servants of Allah and Khalifah on earth. This research highlights that effective management is indispensable for achieving the vision and mission of educational institutions, where good leadership and professional managerial practices are critical success factors. The Quran serves as the primary source that provides comprehensive guidance in the management of education, with particular reference to Surah As-Sajdah which describes God's arrangement of the universe as an example for human beings. Through literature analysis, this research aims to improve understanding of the concept of Islamic education management and develop relevant implementation models in schools. By integrating religious values in managerial practices, it is hoped that educational institutions can produce generations that excel in science and technology while having good morals, making a significant contribution to the progress of Islamic education in the future.